2006
DOI: 10.1080/00365520600610451
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture on the physiology of gastric emptying: A magnetic resonance imaging study

Abstract: The stomach maintains the rate of gastric emptying despite radical changes in body position and intragastric distribution of gastric contents. In SP, hydrostatic pressure (modulated by gastric tone) dictates the gastric emptying. In UDP, gastric emptying also appears to be mediated by continuous adaptation of gastric tone. These findings provide support for the hypothesis that the mechanism of gastric emptying resembles a "pressure pump" rather than a "peristaltic pump". Institute of Diagnostic Radiology, Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 31 publications
2
71
1
Order By: Relevance
“…MRI studies under physiological conditions and after pharmacological modulation of gastric activity have shown that the magnitude of this postprandial relaxation is closely associated with the gastric emptying rate of water and liquid nutrients (20,22). In contrast, the frequency and vigor of antral contractility did not affect this process (20,22,23,34). These findings suggest that gastric emptying is driven by tonic contraction of the gastric fundus, the so-called "pressurepump" hypothesis of gastric emptying (20).…”
mentioning
confidence: 66%
“…MRI studies under physiological conditions and after pharmacological modulation of gastric activity have shown that the magnitude of this postprandial relaxation is closely associated with the gastric emptying rate of water and liquid nutrients (20,22). In contrast, the frequency and vigor of antral contractility did not affect this process (20,22,23,34). These findings suggest that gastric emptying is driven by tonic contraction of the gastric fundus, the so-called "pressurepump" hypothesis of gastric emptying (20).…”
mentioning
confidence: 66%
“…A number of studies have been conducted to clarify the functions of the stomach, particularly focusing on the emptying of gastric contents in the duodenum via the pylorus (13,15,16,17,23). Because changing posture or the ingested volume alters the content location in the stomach, the effects of these parameters on gastric emptying have also been studied extensively (2,4,7,9,14,30). However, even with advances in medical imaging techniques (11,25), visualization of gastric flow is still a difficult task, in particular, with regards to studying gastric mixing in detail.…”
mentioning
confidence: 99%
“…Of note, no changes in gastric emptying could be detected using a 13 C breath test. Since 13 C breath test compares well with the gold-standard scintigraphy [3,5,7,8,23,32], especially for healthy individuals ( [11] and many other studies), our results exclude marked changes in gastric emptying upon HDT [31,35].…”
Section: Discussionmentioning
confidence: 49%